ORALITY IN CIVIL AND FAMILY PROCEDURAL MATTERS IN MEXICO: BRIEF REFLECTIONS ON THE PRINCIPLES GOVERNING IT IN THE NATIONAL CODE - Cota, Norma Dávila (Seven Editora, 2026)
In Mexico, over approximately the last 20 years, oral procedures have progressively been developed in the conduct of jurisdictional processes in certain legal areas; in 2023, the National Code of Civil and Family Procedures was enacted, in which one of its main paradigms is the inclusion of orality as a form of expressing procedural acts; in order to provide a representative and panoramic understanding of the general criteria that guide judicial practice in these relevant matters, the aforementioned legal framework establishes 17 legal principles, which this paper seeks to review by relating them to the principles that guided proceedings under previous legislation and that have also been recognized in legal doctrine; the purpose of this document is to present a brief overview of the current principles, identifying their legal content and contrasting them with classical doctrinal and legal principles.